A Socio-economic Review of the Impacts of Northwest Territories’ Inuvik to Tuktoyaktuk Highway 10 - Fellows, G.; Munzur, Alaz; Winter, Jennifer (Canadian Journal of Regional Science / Revue canadienne des sciences régionales)

(untitled) (Canadian Regional Science Association / Association canadienne des sciences régionales, 2022)
We investigate and project the likely socio-economic effects on the community of Tuktoyaktuk from completion of the all-season Highway 10 (the Inuvik-Tuktoyaktuk Highway) in Northwest Territories, Canada. Prior to the highway’s completion, Tuktoyaktuk was connected to the rest of Canada by air, winter road, and the Mackenzie River in summer. Our analysis is based on estimated relationships between community remoteness and quantifiable socio-economic metrics using the recently developed Index of Remoteness and associated agglomeration data from Statistics Canada (Alasia et al. 2017). Most notable among our results is a statistically strong relationship between agglomeration and both the mean and distribution of household and family incomes, implying that Highway 10 increases incomes across the income distribution. We find similar evidence suggesting increased rates of high school completion. We find no statistically significant relationship between agglomeration and employment participation rates. There is a positive relationship for some forms of crime but no relationship for violent or property crime rates.